Should the Financial Planner Advise His Client to Buy the Life Insurance Policy? - Lim, Chee Chee; Ooi, Sue Chern; Chung, Muh Sha (2022)
The major objective of this teaching case is to let case users apply their knowledge about life insurance and time value of money (TVM) concept in making financial decision. The case illustrates a financial planner (Jack) trying to help his client (Christyn) who does not truly understand life insurance to make a decision whether she should buy the life insurance policy promoted to her by an insurance agent. This teaching case is a decision case in the niche area of economic and financial analysis. It requires the case users to assume the role of Jack (financial planner) to do the following to help Christyn: (a) comparing the cost of insurance (total premium paid) against the different types of benefits (maturity benefit, surrender value and death benefit) provided by the life insurance policy, (b) highlighting the sustainability of the money she has in funding the purchase of the life insurance policy, and (c) providing recommendations whether she should buy the life insurance policy promoted to her by the insurance agent.